Increase in lumbar spine but not distal radius bone mineral density in adults after pancreas kidney transplantation - Kratochvílová, Simona; Maratova, Klara; Sumnik, Zdenek; Brunová, Jana; Hlávka, Zdeněk; Girman, Peter; Saudek, František; Soucek, Ondrej (Bone reports, 2024)
Osteoporosis occurs in every third individual after simultaneous pancreas kidney transplantation (SPKT). Currently used bone measures insufficiently predict their fracture risk. Lumbar spine Trabecular bone score (TBS) and distal radius areal and volumetric bone mineral density (BMD) were monitored for the first time in patients with type 1 diabetes and chronic renal failure after SPKT with steroid-sparing protocol. In 33 subjects (mean age 43.4 ± 9.8 years), dual-energy X-ray absorptiometry and peripheral quantitative computed tomography were performed just after SPKT (baseline) and one and three years later. While TBS Z-scores increased (-1.1 ± 1.2 and -0.3 ± 1.0; p˂0.001, at baseline and year three, respectively), trabecular volumetric BMD Z-scores at distal radius metaphysis did not change during the study (-1.3 ± 1.3 and -1.3 ± 1.0; p = 0.38). Similarly, areal BMD Z-scores increased at lumbar spine, total hip and femoral neck (all p < 0.01), but not at the distal radius. SPKT induced bone measures' improvement at lumbar spine and hip but not at distal radius. Before suggesting changes in current clinical care, predictive value of individual bone measures or its combination for fracture risk assessment remains to be elucidated.